Body temperature and cardiac changes induced by peripherally administered oxytocin, vasopressin and the non‐peptide oxytocin receptor agonist WAY 267, 464: a biotelemetry study in rats. (June 2014) - Hicks, C; Ramos, L; Reekie, T; Misagh, G H; Narlawar, R; Kassiou, M; McGregor, I S
<x xml:space="preserve">Abstract</x> Background and Purpose There is current interest in oxytocin (OT) as a possible therapeutic in psychiatric disorders. However, the usefulness of OT may be constrained by peripheral autonomic effects, which may involve an action at both OT and vasopressin V1A receptors. Here, we characterized the cardiovascular and thermoregulatory effects of OT, vasopressin (AVP) and the non‐peptide OT receptor agonist WAY 267, 464 in rats, and assessed the relative involvement of the OT and V1A receptors in these effects. Experimental Approach Biotelemetry in freely moving male Wistar rats was used to examine body temperature and heart rate after OT (0.01 – 1 mg kg−1; i.p.), AVP (0.001 – 0.1 mg kg−1; i.p.) or WAY 267, 464 (10 and 100 mg kg−1; i.p.). The actions of the OT receptor antagonist Compound 25 (C25, 5 and 10 mg kg−1) and V1A receptor antagonist SR49059 (1 and 10 mg kg−1) were studied, as well as possible V1A receptor antagonist effects of WAY 267, 464. Key Results OT and AVP dose‐dependently reduced body temperature and heart rate. WAY 267, 464 had similar, but more modest, effects. SR49059, but not C25, prevented the hypothermia and bradycardia induced by OT and AVP. WAY 267, 464 (100 mg·kg−1) prevented the effects of OT, and to some extent AVP. Conclusions and Implications Peripherally administered OT and AVP have profound cardiovascular and thermoregulatory effects that appear to principally involve the V1A receptor rather than the OT receptor. Additionally, WAY 267, 464 is not a simple OT receptor agonist, as it has functionally relevant V1A antagonist actions.